Implikasi Pembiasaan Dzikir Terhadap Motivasi Belajar SantriPondok Pesantren An – Nasyiin Grujugan Larangan Pamekasan - Achmad Sayyi (JKI (Jurnal Konseling Indonesia), 2016)
There are two principal issues to be studied in this research; what are the impact of dhikir habituation on students’ learning motivation? and how far the impact of dhikr habituation to motivate students’ learning in An-Nasyiin Boarding school Grujugan Larangan Pamekasan. Type of this research is correlative because it consists of two variables, as the independent variable is habituation of dhikir and as the dependent variable is the motivation to students’ learning with using a study population to 450 people. Thus, of population’s number more than 100 people, then this research conducted as sampling research by taking a sample of 25% with the following detail sampling 450 x 25% = 112.5 is rounded to 113. In addition, This study is using data collection instruments, observations, questionnaires, documentation. Data analysis technique used in analyzing the data is a statistical technique with the formula Yule's Q. The research proves that there is a remembrance of habituation implications on motivation students learning at An-Nasyiin Boarding School Grujugan Larangan Pamekasan. The results of statistical analysis Yule's Q obtained 0.70 which showed a positive correlation between the two variables of this study. In other words, the hypothesis which states: "There are implications of dhikr habituation on students learning motivation of An-Nasyiin Boarding School Grujugan Larangan Pamekasan", accepted as true. To know how far the relationship between the two variables r consulted with the values Q, where r is working on a range of values more then 0.70, which means the impact or influence of both variables are strong significance. Keyword: Dhikir Habituation implications, Students Motivation